EPSPS gene duplication in Palmer amaranth: relative fitness, inheritance, and duplication mechanism of the glyphosate resistance trait - Giacomini, Darci A., author; Westra, Philip, advisor; Ward, Sarah, advisor; Leach, Jan, committee member; Preston, Christopher, committee member; Bedinger, Patricia, committee member (Colorado State University. Libraries, 2015)
Glyphosate resistant (GR) Palmer amaranth (Amaranthus palmeri S. Wats.) is a weedy plant species that has invaded agricultural fields in at least 25 states, raising the cost of weed control to more than 4x the original cost. In most areas, the resistance is conferred through a gene amplification mechanism in which the target gene of glyphosate, 5-enolpyruvylshikimate-3-phosphate (EPSPS) is duplicated in the genome 100+ times, resulting in an overproduction of the EPSPS protein. With so much EPSPS enzyme available in each cell, glyphosate only inhibits a fraction of the proteins, leaving the rest to function as normal and ensuring plant survival. Understanding how this increase in EPSPS gene copy number and EPSPS protein production impacts relative fitness of the resistant plants was one objective of this research. Through greenhouse studies comparing high EPSPS copy GR plants with single copy sensitive plants, no difference was observed for any of the fitness characteristics measured. Both biotypes yielded similar numbers of offspring with no significant differences in germination or growth rate, revealing a complete lack of a fitness cost associated with the resistance trait. The second objective of this research was to quantify the stability of this resistance trait via multigenerational inheritance studies and within-plant EPSPS copy number variance measurements in the absence of glyphosate selection. The inheritance work found a complex pattern of EPSPS copy number transmission through the generations, a result that could be explained at least partially by the mosaic of EPSPS gene copy numbers patterns observed in both male and female Palmer amaranth plants. Copy numbers were inherited in a non-Mendelian pattern with transgressive segregation of the trait seen in both directions (more and fewer EPSPS copies found in the offspring than expected). This retention of high EPSPS copy number in the absence of a glyphosate selection pressure and no evidence of a fitness cost associated with the resistance trait possibly indicates a long-term loss of glyphosate as a control option in fields infested with GR Palmer amaranth. The last objective of this project was to better understand the mechanism of EPSPS gene duplication through sequence assembly of the EPSPS amplicon and chromosomal localization of this duplicated region. The amplicon was extended out to a little over 110kb and was found to contain mostly repetitive sequence including long direct repeats, microsatellites, and multiple transposable elements. A fluorescent in situ hybridization (FISH) assay found a single chromosomal location for the EPSPS genes, suggesting a tandem gene arrangement. These results further suggest that EPSPS duplication is achieved in Palmer amaranth via unequal recombination of the repeats surrounding the gene during mitosis and/or meiosis.
Keywords: glyphosate; fitness; resistance; inheritance; Palmer amaranth